The Effect of Education Self-Care Behaviors on the Hypertension in Postmenopausal Women - Afsar Omidi; Masoud Khodaveisi; Zahra Mirzaei; Maziar Rezvani; Abbas Moghimbeighi (Hamadan University of Medical Sciences, 2017)
Introduction: Hypertension is one of the principal causes of mortality in the world; it imposes heavy costs on the world health's economy. Following the self-care behaviors one can control chronic diseases such as hypertension and its complications can be prevented. This study aimed to determine the effect of education self-care behaviors on the hypertension in  postmenopausal women  referred to Farshchian Hospital in Hamadan was conducted.  Method: This is a quasi-experimental study designed with a control group and before and after measurement. In this study, 70 postmenopausal women with hypertension who were admitted to Farshchian hospital in Hamedan were selected randomly and were put into control and intervention groups. The data were collected using demographic characteristics questionnaire. At first questionnaires were filled by both groups and their blood pressure was measured in both groups. Then, two months after the educational intervention in the experimental group, questionnaires were completed by both groups and blood pressure was measured. To analyze the data Spss software version 20, and paired T test or Wilcoxon equivalent, independent t-test or Mann-Whitney nonparametric equivalent were used. Results: The results showed that the test group average systolic blood pressure and diastolic blood pressure of 147.45 ± 1.25 to 133±.822 and 84.288 ± .71 to 82.14 ±.624 significantly decreased after the intervention. But systolic and diastolic blood pressure, measured before and after the intervention in the control group, didn't show significant difference. Conclusion: The results of this study showed that teaching self-care behaviors is effective in post-menopausal women's control blood pressure. Therefore, self-care education to patients by health care personnel can be used as a low-cost and effective method to be used in health promotion patients